ANALISIS PELAYANAN SERVIS DI BENGKEL NASMOCO CABANG SOLO BARU DENGAN METODE ANTRIAN - Fatma Septy Deviana; Sugito Sugito; Moch. Abdul Mukid (Department of Statistics, Faculty of Science and Mathematics, Universitas Diponegoro, 2014)
World automotive in Indonesia has grown and has a very tight competition. As a company that is in the automotive world and is one of sole agent Toyota in Indonesia to Central Java and Yogyakarta, Nasmoco Solo Baru branch have service and parts facility. As a service provider, Nasmoco Solo Baru branch seeks to serve customers well according to the arrival rate of each customer. Thus, the need to know the measure of system performance on each part on the system service advisor. Queuing system at Nasmoco Solo Baru contained in the Registration Service, Service Parts, and the Cashier Section. Based on the results obtained and the analysis of queuing models are on the Registration Service (M/G/7): (GD/∞/∞) for Monday-Saturday with the booking system and (G/G/7): (GD/∞/∞) for non-booking system, while on Sunday/Holiday booking system model is obtained (M/M/2): (GD/∞/∞) and (M/G/2): (GD/∞/∞) to non-booking system. The model obtained in the service for Monday-Saturday with the booking system and non-booking is (M/G/17): (GD /∞/∞), while on Sunday/Holiday booking system obtained with the model (M/G/9): (GD/∞/ ∞) and (M/M/9): (GD/∞/∞) to the non-booking system. At the cashier queue model for a Monday-Saturday have the same model with a Sunday/Holiday is (M/G/9): (GD/∞/∞). Keywords: Queuing Systems, Nasmoco Solo Baru Branch, Registration Services, Service Parts, Cashier Section.